Challenges in Wood Industries and Contributions of Technological Promotion to Quality Timber Processing in Selected Cities of Ethiopia - Kaba, Gemechu; Hinde, Omer; Hailu, Hiwot; Belachew, Azmera; Ababu, Tesfanesh (Journal of Techno-Social, 2025)
The study investigates the challenges and advantages of technological training in the adoption of advanced methods of timber processing in selected Ethiopian cities, including Addis Ababa, Adama, Hawassa, and Jimma. It examines the impact these technologies have had on the timber industry, identifies the constraints that hamper the full application of the technologies, and describes the prevailing conditions. It applied a mixed-methods approach, where both qualitative and quantitative research were combined. This included interviews with industry experts and site visits to timber processing plants for direct observation. The results indicate that modern technologies have improved the industry in some ways, but a number of drawbacks still exist. These challenges include incorrect or very outdated machinery, absence of professional workers, lack of access to modern technology, and poor infrastructure. The industry also suffers from limited production space and sales areas. In any case, the popularization of new technologies has increased awareness and enhanced the labour skills, especially of producing high-quality lumber in a number of cities. The study also emphasizes technology as a transformative force in Ethiopia's timber industry, and strategic efforts toward resolving current challenges should be embraced on the fronts of technology adoption, training in the workforce, and infrastructure improvement. These are likely to have positive impacts on increasing long-term productivity and economic gains and ensuring environmental sustainability within the industry.